A METAGENOMIC ANALYSIS OF THE GUT MICROBIOTA IN THE KOMODO DRAGON (VARANUS KOMODOENSIS) AND ITS ROLE IN DIGESTION AND IMMUNITY - Aom Thai; Sota Yamamoto; Amanda Wilson (Research of Scientia Naturalis, 2025)
The Komodo dragon (Varanus komodoensis), the largest living lizard, plays a crucial role in its ecosystem. Understanding its gut microbiota is essential for assessing its digestive efficiency and immune function, yet little is known about the microbial communities within its gastrointestinal system. This study aimed to analyze the gut microbiota of wild and captive Komodo dragons using metagenomic sequencing and to explore its role in digestion and immunity. Fecal and gut content samples were collected from 12 wild and 10 captive Komodo dragons. High-throughput sequencing of the 16S rRNA gene was used to characterize the microbial diversity. The results revealed significant differences in microbiota composition between wild and captive individuals, with wild dragons displaying higher microbial diversity. Dominant phyla in wild Komodo dragons included Firmicutes and Bacteroidetes, while Escherichia and Klebsiella were more prevalent in captive individuals. Additionally, microbial diversity was positively correlated with immune-related gene expression, suggesting that the microbiota plays a role in immune modulation. These findings highlight the importance of diet and environmental factors in shaping the gut microbiota, with implications for conservation and breeding programs. Further research should focus on functional profiling and exploring other microbial groups to fully understand the microbiome's impact on health